Ferns and lycophytes from Cerro da Pedra do Lagarto, Santa Maria, Rio Grande do Sul, Brazil - Schindler, Bianca (2021)
The inventory of ferns and lycophytes was carried out in Cerro da Pedra do Lagarto, a vegetation refuge with distinct phytophysiognomies (forest and natural grassland, respectively) located in the district of Santo Antão, North of the Municipality of Santa Maria, Rio Grande do Sul State. The aim of this study was to contribute to the knowledge of the flora of fern and lycophytes in the poorly sampled central Region of the State, supplying ecologic and biological data and a dichotomous key for the identification of the species observed. There are 34 fern species and two lycophyte species, belonging to 28 genera of 14 botanical families. Polypodiaceae was the richest family with eight species, followed by Pteridaceae, with seven. Most species were terrestrial and the only arborescent specie was Cyathea atrovirens. The inventoried data represent 9.5% of the known species of ferns and lycophytes for the State of Rio Grande do Sul.